2009
DOI: 10.1155/2009/426346
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Melatonin on Cerebrovascular Proinflammatory Mediators Expression and Oxidative Stress Following Subarachnoid Hemorrhage in Rabbits

Abstract: The aim of this study is to analyze whether melatonin administration influenced the nuclear factor-kappa B (NF-κB) activity, proinflammatory cytokines expression, and oxidative response in the basilar artery after SAH. A total of 48 rabbits were randomly divided into four groups: control group, SAH group, SAH + vehicle group, and SAH + melatonin group. All SAH animals were subjected to injection of autologous blood into cisterna magna twice on day 0 and day 2. The melatonin was administered intraperitoneally a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 19 publications
3
30
0
Order By: Relevance
“…The malondialdehyde (MDA) levels were determined using the method of a previous study. 8 The principle of the assay depends on the reaction of lipid peroxidation products with thiobarbituric acid and formation of products called thiobarbituric acid-reacting substances, which give maximum absorbance at the 535-nm wavelength. The MDA concentrations were given as nanomoles/milligram protein.…”
Section: Biochemical Estimationmentioning
confidence: 99%
“…The malondialdehyde (MDA) levels were determined using the method of a previous study. 8 The principle of the assay depends on the reaction of lipid peroxidation products with thiobarbituric acid and formation of products called thiobarbituric acid-reacting substances, which give maximum absorbance at the 535-nm wavelength. The MDA concentrations were given as nanomoles/milligram protein.…”
Section: Biochemical Estimationmentioning
confidence: 99%
“…Several studies with cells, tissues, and whole animals have shown that melatonin inhibits NF-κB either by oxidative stress or PAMPs. Melatonin reduces NF-κB activation in macrophages [42], T cells [43,44], RAW 264.7 cell line [4547], neuronal tissue and cell culture [4749], liver [50], kidney [51,52], lung [53], and heart [54]. Studies based on models of inflammatory disease, such as inflammatory bowel disease [55], colitis [56], chronic gastric ulceration model in mice [57], and experimental diabetic neuropathy [58] as well as inflammatory processes, such as hyperalgesia associated with inflammation [59], spinal cord trauma [60], and fulminant hepatic failure [50] in rats describe a reduction of inflammatory output by melatonin.…”
Section: Melatonin and The Regulation Of Nf-κb Activationmentioning
confidence: 99%
“…Studies based on models of inflammatory disease, such as inflammatory bowel disease [55], colitis [56], chronic gastric ulceration model in mice [57], and experimental diabetic neuropathy [58] as well as inflammatory processes, such as hyperalgesia associated with inflammation [59], spinal cord trauma [60], and fulminant hepatic failure [50] in rats describe a reduction of inflammatory output by melatonin. In addition, when evaluated, the anti-inflammatory effect of melatonin was shown to be mediated by the inhibition of NF-κB nuclear translocation [42,49,54,6163]. …”
Section: Melatonin and The Regulation Of Nf-κb Activationmentioning
confidence: 99%
“…Malondialdehyde (MDA) levels were determined with the method of the previous study (Fang et al, 2009). The principle of the assay depends on the reaction of lipid peroxidation products with thiobarbituric acid and formation of products named as thiobarbituric acid reacting substances, which give maximum absorbance at 535 nm wavelength.…”
Section: Malondialdehyde Estimationmentioning
confidence: 99%